Genome-wide analysis of 14-3-3 gene family in four gramineae and its response to mycorrhizal symbiosis in maize - Wang, Yanping; Xu, Qiang; Shan, Hanchen; Ni, Ying; Xu, Minyan; Xu, Yunjian; Cheng, Beijiu; Li, Xiaoyu (Frontiers in Plant Science, 2023)
14-3-3 proteins (regulatory protein family) are phosphate serine-binding proteins. A number of transcription factors and signaling proteins have been shown to bind to the 14-3-3 protein in plants, which plays a role in regulating their growth (seed dormancy, cell elongation and division, vegetative and reproduction growth and stress response (salt stress, drought stress, cold stress). Therefore, the 14-3-3 genes are crucial in controlling how plants respond to stress and develop. However, little is known about the function of 14-3-3 gene families in gramineae. In this study, 49 14-3-3 genes were identified from four gramineae, including maize, rice, sorghum and brachypodium, and their phylogeny, structure, collinearity and expression patterns of these genes were systematically analyzed. Genome synchronization analysis showed large-scale replication events of 14-3-3 genes in these gramineae plants. Moreover, gene expression revealed that the 14-3-3 genes respond to biotic and abiotic stresses differently in different tissues. Upon arbuscular mycorrhizal (AM) symbiosis, the expression level of 14-3-3 genes in maize significantly increased, suggesting the important role of 14-3-3 genes in maize-AM symbiosis. Our results provide a better understanding on the occurrence of 14-3-3 genes in Gramineae plants, and several important candidate genes were found for futher study on AMF symbiotic regulation in maize.